PENGARUH MODEL PEMBELAJARAN SOMATIC, AUDITORY, VISUAL, INTELLECTUAL TERHADAP KEMAMPUAN METAKOGNITIF DAN KECERDASAN EMOSIONAL PADA MATERI SISTEM EKSKRESI KELAS VIII DI MTsN - Aryani Dwi Kesumawardani; Fitri Nurmalasari; Heru Juabdin Sada; Raicha Oktafiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the effect of the Somatic, Auditory, Visual, Intellectual learning model on the metacognitive ability and emotional intelligence of eighth-grade students at MTsN 1 Bandar Lampung. This study was driven by the low metacognitive ability and emotional intelligence observed among students, as indicated by pre-research scores. This condition was mainly influenced by conventional learning processes that lacked active student participation, thus necessitating a contextual innovation to enhance more active, meaningful, and sustainable engagement. The research method used was a quasi-experimental approach with a posttest-only control design. The research sample was obtained using cluster random sampling, involving two classes, namely class VIII A as the experimental class, which implemented the Somatic, Auditory, Visual, Intellectual learning model, and class VIII B as the control class, which applied the Discovery Learning model. The instruments used in this study consisted of essay questions to measure metacognitive ability and a questionnaire to assess emotional intelligence. The data analysis technique employed was the Independent Sample T-Test. Based on the hypothesis testing results, the Sig. (2-tailed) value obtained was 0.000 < 0.05, indicating that the implementation of the Somatic, Auditory, Visual, Intellectual learning model had a significant effect on improving students’ metacognitive ability and emotional intelligence at MTsN 1 Bandar Lampung. Therefore, the Somatic, Auditory, Visual, Intellectual learning model is effective in enhancing metacognitive ability and emotional intelligence.